Kinetic Modeling for Microwave-Enhanced Degradation of Methylene Blue Using Manganese Oxide - Wen-Hui Kuan; Chun-Yuan Chen; Ching-Yao Hu; Yu-Min Tzou (International Journal of Photoenergy)
This study was originally performed to compare the MnO2-based degradation of aqueous methylene blue (MB) under microwave irradiation- (MW-) enhanced and conventional heating- (CH-) enhanced conditions. The degradation process and kinetics were investigated to elucidate the microwave effect on the reaction. The results showed that all three tested conditions, sole MnO2, MnO2/CH, and MnO2/MW, followed the third-order (second upon MB and first upon MnO2) kinetic model. However, a higher degradation rate of MB was available under the MW-enhanced process, which implies that the “athermal effect” of MW might be of more benefit for the generation of electrophilic oxygen ions (, , and ) to degrade MB. The results showed that the degradation percentage of MB could reach 100%, corresponding to 92% total organic carbon (TOC) removal under microwave irradiation at pH 7.20 for 10 min.